Bounds on Higgs and gauge-boson interactions from LEP2 data - Éboli, O. J P [UNESP]; Gonzalez-Garcia, M. C. [UNESP]; Lietti, S. M. [UNESP]; Novaes, Sérgio Ferraz [UNESP] (Elsevier, 1998)
We derive bounds on Higgs and gauge-boson anomalous interactions using the LEP2 data on the production of three photons and photon pairs in association with hadrons. In the framework of SU(2)L ⊗ U(1)Y effective Lagrangians, we examine all dimension-six operators that lead to anomalous Higgs interactions involving γ and Z. The search for Higgs boson decaying to γγ pairs allow us to obtain constrains on these anomalous couplings that are comparable with the ones originating from the analysis of pp̄ collisions at the Tevatron. Our results also show that if the coefficients of all blind operators are assumed to have the same magnitude, the indirect constraints on the anomalous couplings obtained from this analysis, for Higgs masses MH ≲ 140 GeV, are more restrictive than the ones coming from the W+W- production. © 1998 Elsevier Science B.V. All rights reserved.